Duolingo Application as A Mean to Deepen Understanding of English Vocabulary by Students of English Educational Department Timor University - Siahaan, Desta Gloria; Nahak, Maria Hendrika Kristen Indi; Bouk, Edmundus (P3KM Politeknik Pertanian Negeri Samarinda, 2024)
This study aimed to explain the role of the Duolingo application in improving English vocabulary comprehension and to provide valuable insights for educators regarding the potential of digital applications in English language learning. The Duolingo application is expected to help students of the third semester from English Educational Department at Timor University to deepen their understanding of English vocabulary. This research used a qualitative approach, the instruments used in this research were a vocabulary test and a questionnaire. The results of the vocabulary test showed that students who used the Duolingo application had a better understanding of vocabulary. The average test score was 76.7, with the highest was 93.38, indicating that the use of this application was able to provide a deep understanding of vocabulary, the lowest score was 66.7. The results from the questionnaire revealed that 50% of students strongly agreed and 50% agreed that Duolingo helped them quickly correct mistakes after each exercise. However, 60% of students felt that the application's features had a minimal effect on improving their learning experience, while 30% strongly disagreed. In terms of engagement, 60% of students regularly used the Duolingo application to learn English, while 40% did not. Furthermore, 80% of students felt that learning English became easier with Duolingo, while 20% agreed. 50% of students strongly agreed that the features within the application assisted in the learning process, while the other 50% agreed. 50% of students felt more enthusiastic about learning with this application, and the other 50% also agreed. The engagement and flexibility of the application were recognized as motivating factors for students to continue learning, with 50% strongly agreeing and 50% agreeing. However, there were challenges related to the use of community features. Only 20% of students strongly agreed that they were engaged with community features such as forums or study groups, while 40% disagreed and 40% strongly disagreed. On the other hand, 60% of students felt that motivational elements such as rewards and challenges influenced how often they used the application to study. In conclusion, the Duolingo application proved to be effective in deepening English vocabulary comprehension among third semester students of the English Educational Department at Timor University. This research provided valuable insights into the effectiveness of the Duolingo application as a tool for learning English vocabulary among students.